Peningkatan Literasi Kewirausahaan Berbasis Data bagi Mahasiswa Internasional - Indra Arifin Djashan; Denta Felli Ananda; Arton Bryan Prasetyo (Universitas Muhammadiyah Palembang, 2026)
This community service activity aims to improve international students' understanding of data-driven entrepreneurship through a guest lecture program delivered by lecturers from STIE Trisakti, Jakarta, to college and high school students at Burapha University International College (BUUIC), Thailand. The session, themed